2015
DOI: 10.3390/en8043212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Model Simplifications Excitation Force in Surge for a Floating Foundation for Offshore Wind Turbines

Abstract: Abstract:As offshore wind turbines move towards deeper and more distant sites, the concept of floating foundations is a potential technically and economically attractive alternative to the traditional fixed foundations. Unlike the well-studied monopile, the geometry of a floating foundation is complex and, thereby, increases the difficulty in wave force determination due to limitations of the commonly used simplified methods. This paper deals with a physical model test of the hydrodynamic excitation force in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…At present, the well-known modular system is ETAP Wind Turbine Modeling (WTM) software [23], which is used to design and monitor wind farms in a flexible graphic interface optimized for wind power simulation and analysis. Andersen, Hindhede [24] indicated that the Swim-Motion-Lines (SML) software suite is applicable to the maritime and offshore industries for calculating motion responses of floating platforms in winds, waves, or currents. SML is composed of three modules: the SWIM module is used to calculate hydrodynamic forces in the frequency domain; the MOTION module is adopted to simulate a slow-drift response in the time domain; and the LINES module is employed to estimate the influence of the mooring system on the floating platform.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the well-known modular system is ETAP Wind Turbine Modeling (WTM) software [23], which is used to design and monitor wind farms in a flexible graphic interface optimized for wind power simulation and analysis. Andersen, Hindhede [24] indicated that the Swim-Motion-Lines (SML) software suite is applicable to the maritime and offshore industries for calculating motion responses of floating platforms in winds, waves, or currents. SML is composed of three modules: the SWIM module is used to calculate hydrodynamic forces in the frequency domain; the MOTION module is adopted to simulate a slow-drift response in the time domain; and the LINES module is employed to estimate the influence of the mooring system on the floating platform.…”
Section: Introductionmentioning
confidence: 99%